Perceptions of research burden reported by study partners of longitudinal ADC cohort participants: Epidemiology / Innovative methods in epidemiology (i.e., assessment methods, design, recruitment strategies, statistical methods, etc.). (7th December 2020) - Edwards, Dorothy Farrar; Lingler, Jennifer; Chin, Erin; Gabel, Matthew; Coble, Dean W; Grill, Josh D; Stark, Susan
Abstract: Background: Study partners are required for all ADC Clinical Core participants, they provide valuable information about cognitive and functional status of enrolled participants, which is essential for CDR ratings and documentation of perceived cognitive changes over time. Retention of participants and their SPs is essential for unbiased longitudinal data, yet little is known of SP attitudes and beliefs and how these attitudes influence missed visits or overall attrition. This mixed methods study identified SPs perceived barriers and facilitators related to participant retention in longitudinal ADC studies Method: Methods: A 57 item survey with 2 open ended questions was administered by telephone to randomly selected study partners (N=210) from four NIA funded Alzheimer's disease Centers. The Perceived Research Burden Assessment (PeRBA) was included in the survey. Respondents were 51% female, mean age was 72±8.6 ( 52‐92yrs), 92% were spouses. Response frequencies were computed for each item, open ended responses were transcribed, and thematically coded. Result: Study partners report high levels of trust in medical researchers (88%), high levels of altruism they believe their participation is valuable (96%) and society benefits from their research participation (98%). Low levels of overall burden were associated with ADC participation. Most negative attitudes were associated with travel (14%), inconvenience reaching the research center (15%) and length of study visits (17%). They also reported that their last LP (18%) and memory testing (19%) visits were difficult, with physical pain (13%) and fatigue (16%) as most common post‐assessment problems. A substantial number (83%) had difficulty keeping track of different study procedures. Only 37% reported being invited to participate in additional ADC‐sponsored studies. Thematic analyses identified common concerns/suggestions across ADC sites including: more frequent feedback and information about study results, evidence‐based caregiving advice, more complete disclosure of individual findings, better coordination and communication around multiple study visits and high praise for research staff. Conclusion: Study partners are critical to longitudinal retention of ADC participants. SP loss accounts for a significant proportion of missed visits or outright attrition. Changing study partners contributes to greater variability in longitudinal data. Our findings emphasize the importance of attending to the concerns of study partners in retention programs.